Leaders' Reactions to 360° Feedback: Examining Individual Attributes and Format Effects - Allison Traylor; Denise Reyes; Katelyn Cavanaugh; Courtney Holladay (International School for Social and Business Studies, 2021)
Purpose: Numerous studies have explored the role of feedback format, and individual differences in influencing reactions to and behavior change following the receipt of 360° feedback. Recent research has considered the role that implicit theories of ability play in reactions to negative feedback. The current study replicates and extends this work, investigating the interaction between implicit theories of ability, feedback format (i.e., the inclusion of normative or normative and narrative feedback), and feedback valence as they relate to feedback reactions. Study design/methodology/approach: We conducted a quasi-experimental study of leaders in a large healthcare organization in the United States. Findings: We found that the interaction between implicit theories of ability and feedback format is dependent on feedback valence. Though implicit theories of ability moderate the relationship format and reactions for negative feedback, the effect did not hold when individuals received positive feedback. In addition, we did not find a statistically significant impact of normative and narrative (versus normative) feedback on reactions. Originality/value: This study extends our understanding of individual differences and feedback format in predicting reactions to feedback, providing important implicatins for both theory and practice.